2018
DOI: 10.1111/njb.01728
|View full text |Cite
|
Sign up to set email alerts
|

Ecological data for an orchid diversity hotspot show that the subtribe Laeliinae may be endangered in the Brazilian Atlantic Forest

Abstract: The Brazilian Atlantic Forest harbours a mega diversity of seed plants. The Parque Nacional do Itatiaia is a large and mature Atlantic Forest remnant in southeastern Brazil. It includes around 10% of the Brazilian orchids and is considered a priority area for conservation. Thirty‐three species of the neotropical and very ornamental subtribe Laeliinae (Orchidaceae) have been recorded in this park, but according to our studies 13 species may be extinct locally. Here, we present ecological information, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…The other species have not yet been evaluated, but, as they have wide geographic distributions, it is likely that they are also not at imminent risk of extinction. Nonetheless, many Orchidaceae species are subject to predatory collection due to their high ornamental value, often resulting in population reduction or local suppression, this scenario being more likely in areas where the plants are more easily accessed (Cruz et al, 2003;Barberena et al, 2018a), as is the case with restingas. In the PNMR Praia do Forte, we observed that some species have small populations (<50 individuals) and restricted local distribution, and, therefore, require the attention of managers, in order to implement possible management and conservation actions and prevent them from being suppressed locally.…”
Section: Discussionmentioning
confidence: 99%
“…The other species have not yet been evaluated, but, as they have wide geographic distributions, it is likely that they are also not at imminent risk of extinction. Nonetheless, many Orchidaceae species are subject to predatory collection due to their high ornamental value, often resulting in population reduction or local suppression, this scenario being more likely in areas where the plants are more easily accessed (Cruz et al, 2003;Barberena et al, 2018a), as is the case with restingas. In the PNMR Praia do Forte, we observed that some species have small populations (<50 individuals) and restricted local distribution, and, therefore, require the attention of managers, in order to implement possible management and conservation actions and prevent them from being suppressed locally.…”
Section: Discussionmentioning
confidence: 99%
“…Las especies de orquídeas son particularmente vulnerables a la extinción, ya que, entre otros factores, con frecuencia tienen poblaciones reducidas, con una distribución restringida, y dependen al menos parcialmente de los hongos, principalmente, con respecto a la germinación y el desarrollo de plántulas (Batty et al, 2001;Barros, 2007;Pandey et al, 2013). Además, están sujetas a colecciones depredadoras por coleccionistas y comerciantes, que alimentan el comercio ilegal activo (Barros et al, 2007;Barberena et al, 2018).…”
Section: Introductionunclassified